How Do the Labour Force Characteristics Encounter COVID-19 Economic Consequences—A Canadian Experience - Arsena Gjipali; Valbona Karapici; Nevila Baci (Administrative Sciences, 2023)
This paper draws on a current international analysis of pandemic consequences in the labour market and on the way different segments have been impacted. The purpose is to provide a critical investigation of the facts and arguments regarding how and why the consequences of the same health epidemic are differently faced at an uneven socio-economic burden. The objectives are twofold: First, we aim to explore on an international level the inequality settings that COVID-19 has highlighted, focusing on the most affected economic pillars such as the labour market. Second, we provide an empirical analysis of the likelihood of Canadian labour force participants to be unemployed before and after COVID-19, as one of the measurable effects of the pandemic. We assess how the likelihood of the working-age population falling into the unemployment pool varies before, during and immediately after the pandemic restrictions ease, using Canadian Labour Force Survey microdata. The findings indicate that mainly immigrants and youth suffered the most, pointing out their probably higher participation in precarious jobs and calling for policy initiatives to fix the structural faults in the labour market.